The Effects of Daylight Saving Time on Traffic Accidents in the Czech Republic - Litomerický, Jakub; Chytilová, Helena; Kotrba, Vojtěch; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
Daylight Saving Time (DST) transitions have long been a subject of debate regarding their societal impacts. This thesis investigates the relationship between the spring DST transitions and traffic accidents in the Czech Republic. The theoretical framework explores the importance of sleep, the effects of sleep deprivation, and the societal implications of DST transitions. Additionally, the study focuses on the definition and occurrence of traffic accidents with an analysis of biological, environmental, and societal factors. The practical part employs a regression analysis using the Ordinary Least Squares (OLS) method. Data from the Czech police, Czech Hydrometeorological Institute, and Sunrise and Sunset Time Organization are used. Multiple variables are used in the model, including the number of weekly accidents as the endogenous variable, and a dummy week_after as the exogenous variable, representing the week after the spring transition into DST. The regression results reveal a significant model with an R-squared value of 0.51. All variables are significant at the 5% significance level except the exogenous variable, suggesting that the spring transition into DST may not directly impact the incidence of traffic accidents in the following week in the Czech Republic. Further analysis indicates that school holidays and mobility restrictions have a negative impact on accident rates, while average week temperature, time, and precipitation exhibit positive effects. The average weekly temperature came out as the variable with the biggest impact on the incidence in the Czech Republic.
Vedoucí práce: Helena Chytilová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses